PENGARUH PERSEPSI KUALITAS LAYANAN DAN SIKAP NASABAH TERHADAP KEPUTUSAN MENGGUNAKAN LAYANAN MOBILE BANKING (STUDI KASUS PADA BANK BNI KCU JAKARTA PUSAT) - Dinda Ayu Fadhillah; Sugeng Prayetno (Bajang Institute, 2023)
When a bank offers mobile banking services, they provide their customers with tools that facilitate the use of online banking from anywhere and at any time. This quantitative study aims to find out how Perceived Quality of Service (SQ) (X1) and Customer Attitudes (X2) on the Decision to Use Mobile Banking Services (Y). One hundred mobile banking users at Bank BNI KCU Central Jakarta branch were surveyed via a questionnaire. Based on the findings of this study, Perceived Service Quality (SQ) and Customer Attitudes have a positive and significant effect on the Decision to Use Mobile Banking Services at Bank BNI KCU Central Jakarta, either partially or simultaneously. The magnitude of the influence of 74.8% of the variable Service Quality (SQ) and Customer Attitudes can affect the Decision to Use Mobile Banking Services at Bank BNI KCU Central Jakarta, while the remaining 25.2% is influenced by other variables outside of this research